Vaccines for African swine fever: an update - Zhang, Hongliang; Zhao, Saisai; Zhang, Haojie; Qin, Zhihua; Shan, Hu; Cai, Xiulei (Frontiers in Microbiology, 2023)
African swine fever (ASF) is a fatal infectious disease of swine caused by the African swine fever virus (ASFV). Currently, the disease is listed as a legally notifiable disease that must be reported to the World Organization for Animal Health (WOAH). The economic losses to the global pig industry have been insurmountable since the outbreak of ASF. Control and eradication of ASF are very critical during the current pandemic. Vaccination is the optimal strategy to prevent and control the ASF epidemic, however since only very poor immune protection was induced by inactivated ASF vaccines and no enough cell lines we have for efficient ASFV replication in vitro, an ASF vaccine with high effective immuno-protection still remains to be explored. Knowledge of the course of disease evolution, the way of virus transmission, and the breakthrough point of vaccine design will help us on ASF vaccine development. This review aims to highlight the recent advances and breakthroughs in the epidemic and transmission of ASF, virus mutation, and the development of vaccines in recent years, focusing on future directions and trends.